The impact of emotion-focused therapy interventions on wound care anxiety in a pediatric patient with severe burns: a case report - Cameron Miller; Isaac Edwards; Monica Osterbauer; Sydney Crane; Jennifer Kesey; John Griswold (Burns Open)
Pediatric burn injuries result in observable psychological distress, including heightened anxiety, pain response, and behavioral challenges, which can impede recovery. This case study explores the application of Emotion-Focused Therapy as a nonpharmacologic intervention to reduce wound care anxiety. Our case involved a 7-year-old female recovering from 54 % total body surface area third-degree burns sustained in a car accident. The patient exhibited severe anticipatory anxiety, panic attacks, and avoidance behaviors during dressing changes, with frequent sedation that prolonged the recovery process. An integrated behavioral health provider, specifically a Licensed Marriage and Family Therapist used Emotion-Focused Therapy interventions targeting emotional awareness and regulation. Techniques such as deep breathing, guided imagery, music therapy, and patient empowerment through active participation in wound care were employed to address the patient’s emotional distress. Emotion-Focused Therapy interventions helped transform the patient’s experience and led to improved psychological outcomes including notably reduced anxiety, decreased dependency on sedative medications, improved cooperation during wound care, and subjectively faster emotional stabilization. Behavioral changes were evident as the patient demonstrated increased emotional regulation, self-efficacy, and active involvement in her care, as noted by nursing staff and family members. This case highlights the critical role of integrating psychological interventions, such as Emotion-Focused Therapy, into pediatric burn treatment to address the emotional and physical challenges of recovery.